Penerapan Metode SAW (Simple Additive Weight) Dalam Sistem Pendukung Keputusan Pemilihan Internet Service Provider - Taufik Kurnialensya Kurnialensya; Eko Siswanto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The use of internet network services is currently in high demand in various sectors, ranging from education, business, households, government, banking, industry, large companies, healthcare, entertainment and media, transportation, and public spaces. The SAW algorithm method is used to assist in making decision-making recommendations to determine internet services from providers that are more objective, accurate, and supported by good service. From the results of the research using four alternatives, namely ISP1, ISP2, ISP3, and ISP4, each alternative has the following weight values: ISP1 has a value of 83.54, ISP2 has a value of 87.80, ISP3 has a value of 87.75, and ISP4 has a value of 92.56. Therefore, the best alternative is ISP4 as the best internet service provider.